4 times 6 is equal to 24 so I did the same to 5 ( because 4/5) and then I got 30 so.
In six years he will be 24 and his brother will be 30 but in 4 years his brother Nick will be 28.
f(x) = (x- zero) * (x -zero)
f(x) = (x--2) (x-8)
f(x) = (x+2) (x-8)
if you need it multiplied out
f(x) = x^2 +2x -8x-16
f(x) = x^2 -6x-16
Answer:
-13.85
Step-by-step explanation:
-7.28+-11.17= -18.45
-18.45+4.6= -13.85
Answer:
y = 5.5x - 17
Step-by-step explanation:
(4,5)(2,-6)
- M = ∆y/∆x
- -6-5/2-4
- -11/-2 this is the gradient
- chose any of the point then introduce another point
- (4,5) (x,y) the gradient is -11/-2
- M =∆y/∆x
- y-5/x-4 = -11/-2
- -2(y-5) = -11 ( x -4)
- -2Y + 10 = -11x + 44
- -2Y = -11x + 44 -10
- -2Y = -11x + 34
- divide the while equation by -2
- y = 5.5x + - 17
- y= 5.5x - 17
<u>ANSWER</u>
![f(x) = 2 ({x - 1)}^{2} - 1](https://tex.z-dn.net/?f=f%28x%29%20%3D%202%20%28%7Bx%20%20-%201%29%7D%5E%7B2%7D%20-%201)
<u>EXPLANATION</u>
The vertex form of a parabola has equation:
![f(x) = a ({x - h)}^{2} + k](https://tex.z-dn.net/?f=f%28x%29%20%3D%20a%20%28%7Bx%20%20-%20h%29%7D%5E%7B2%7D%20%20%2B%20k)
where V(h,k) is the vertex of the parabola and 'a' is the leading coefficient.
From the question, we have that, the vertex is
![(1,-1)](https://tex.z-dn.net/?f=%281%2C-1%29)
and the leading coefficient is
![a= 2](https://tex.z-dn.net/?f=a%3D%202)
We substitute the vertex and the leading coefficient into the vertex form to get:
![f(x) = 2 ({x - 1)}^{2} + - 1](https://tex.z-dn.net/?f=f%28x%29%20%3D%202%20%28%7Bx%20%20-%201%29%7D%5E%7B2%7D%20%20%2B%20%20-%201)
We simplify to get:
![f(x) = 2 ({x - 1)}^{2} - 1](https://tex.z-dn.net/?f=f%28x%29%20%3D%202%20%28%7Bx%20%20-%201%29%7D%5E%7B2%7D%20-%201)
The graph of this function is shown in the attachment.